PUBLIC RELATIONS AN ATTEMPT TO BUILD A DEFINITION - Hadi, Haytham (ALBAHITH ALALAMI, 2008)
This research deals with the most famous existing definitions of public relations, in an attempt to achieve a definition that will be added to the other existing and widespread definitions, especially that big developments have taken place in the concept of public relations and their idiomatic use. In addition, many definitions of public relations have been restricted to some limited descriptions, therefore many of the descriptions given to the public relations are basically definitions as well as characteristics of the public relations. This research aims at setting and formulating the definitions of public relations, it also deals with its credibility in achieving its significance in order to reach a new definition that will be added to the rest of the definitions; meanwhile, making sure that the new definition complements to the other definitions rather than just being an addition, especially that science is known by accumulation. Although there are differences between the definitions, these differences are disappearing continuously due to the exchange of opinions and thanks to research, we are able to attain some results which are closer to those differences, especially that the research centers and the governmental bodies are continuing their efforts in this field to give an approximation to the definitions in order to facilitate their use in science and theory to become more meticulous. The problem of the research is that an agreement on the definition of public relations has not been achieved, there are also big differences between the definitions that’s what makes the access to approximate definitions a crucial scientific demand, in a way that this definition fulfills the diversity and flexibility of public relations’ functions, especially that public relations aim at establishing and maintaining good relations between an organization and its public. Every organization is affected by its audience which affects it in return, it is also interested in having a friendly and understanding relationship with it. Today, organizations of all kinds, whether public or private, commercial or social, are seeking to have the satisfaction and the cooperation of their audience.